Barbie. A perfect Christmas [videorecording (DVD)] - Baldo, Mark (Universal Studios Home Entertainment, 2011)
Join Barbie and her sisters Skipper, Stacie, and Chelsea as their holiday vacation plans turn into a most unexpected adventure and heartwarming lesson. After a snowstorm diverts their plane, the girls find themselves far from their New York destination and their holiday dreams. Now stranded at a remote inn in the tiny town of Tannenbaum, the sisters are welcomed by new friends and magical experiences.